Research progress on nanocellulose and its composite materials as orthopedic implant biomaterials - Tiehui Shen; Hao Dong; Pan Wang (Alexandria Engineering Journal, 2024)
This review summarizes recent progress on nanocellulose and its composite materials as emerging biomaterials for orthopedic implant applications. The three main types of nanocellulose - cellulose nanocrystals (CNCs), cellulose nanofibrils (CNFs) and bacterial nanocellulose (BNC) possess exceptional mechanical properties exceeding traditional implant materials like metals, ceramics and polymers. Their high strength, stiffness, porosity, surface area, hydrophilicity and biocompatibility make nanocellulose well-suited as a scaffold material for bone regeneration. This review covers the fabrication of nanocellulose-based composites with ceramics and polymers to further enhance their mechanical performance and bioactivity. Various methods are utilized to develop nanocellulose implants and scaffolds with controlled architecture optimized for bone ingrowth. In vitro studies demonstrate nanocellulose supports stem cell osteogenic differentiation and growth. In vivo results in animal models show bone regeneration in critical sized defects, though challenges remain in vascularization. While further research is required to control degradation and scale up manufacturing, nanocellulose has strong potential to address limitations of current orthopedic implants as the next generation of high performance biomaterials. This review provides a comprehensive perspective on the state-of-the-art in nanocellulose materials for advanced orthopedic implants.